Larvicidal effect of Pongamia pinnata plant extracts against Papilio demoleus Linnaeus (Insecta: Lepidoptera: Papilionidae) - LINGAKARI, MAHESH; MADDALA, MADHAVI; BANDI, SRIKANTH (Journal of Biological Control, 2023)
Larvae of the citrus butterfly, Papilio demoleus are serious pests in citrus orchards. Since synthetic pesticides have several ill effects on human health and the ecosystem, biopesticides are feasible alternative to synthetic pesticides. Indian beech tree, Pongamia pinnata plant extracts are well known for their medicinal and pesticidal properties. So, a study was carried out to evaluate P. pinnata plant’s aqueous leaf and seed extracts, and seed oil nanoemulsion at 25, 50, 100, 200, and 400 PPM concentrations against the 4th instar larvae of P. demoleus. All three test compounds showed concentration-dependent larvicidal activity. Comparatively, leaf extracts showed better larvicidal activity than seed extracts and nanoemulsion of the seed oil. The highest mortality was observed with leaf, seed extracts, and seed oil emulsions at 82.61%, 78.26%, and 73.91% respectively, at 400 PPM concentration. LC50 and LC90 values were lowest for leaf extracts (57.97 and 855.93 PPM), while the highest for seed oil nanoemulsion (107.09 and 1947.90 PPM). This is the first report of the efficacy P. pinnata leaf and seed extracts and seed oil nano emulsions against 4th instar larvae of P. demoleus.